Reply to: Comment on: Geriatric co‐management for cardiology patients in the hospital: A quasi‐experimental study. Issue 8 (27th June 2021) - Van Grootven, Bastiaan; Milisen, Koen; Flamaing, Johan; Deschodt, Mieke
Abstract : This letter comments on the letter by Issei Kameda in this issue.